2021
DOI: 10.1186/s12872-021-02380-0
|View full text |Cite
|
Sign up to set email alerts
|

Inverse correlation between serum irisin and cardiovascular risk factors among Chinese overweight/obese population

Abstract: Background Irisin is a novel myokine associated with obesity, which is a traditional cardiovascular risk factor (CVRF). The present study aimed to investigate the association between serum irisin and a single CVRF as well as the clustering of CVRFs among Chinese overweight/obese population. Methods A total of 98 overweight and 93 obese subjects without clinical treatments were enrolled in this study. Subjects were then divided into two groups, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…High Irisin levels have been found to be associated with better control of hypertension and T2DM in various studies. (21,22). Despite the diversity in our patient group regarding the presence of hypertension and T2DM, probably due to the effects of natural aging, regression analyses indicated that systemic disorders had no signi cant effect on Irisin levels among the patient population.…”
Section: Discussionmentioning
confidence: 99%
“…High Irisin levels have been found to be associated with better control of hypertension and T2DM in various studies. (21,22). Despite the diversity in our patient group regarding the presence of hypertension and T2DM, probably due to the effects of natural aging, regression analyses indicated that systemic disorders had no signi cant effect on Irisin levels among the patient population.…”
Section: Discussionmentioning
confidence: 99%
“…The subject inclusion criteria were as follows: 1) the diagnosis of T2DM was based on the latest American Diabetes Association guidelines for the diagnosis and treatment of diabetes; 36 2) all patients were aged ≥18 years and ≤80 years; 3) subjects had a body mass index (BMI) <28 kg/m 2 , which met the Chinese diagnostic standard for non-obesity. 37 …”
Section: Methodsmentioning
confidence: 99%
“…The subject inclusion criteria were as follows: 1) the diagnosis of T2DM was based on the latest American Diabetes Association guidelines for the diagnosis and treatment of diabetes; 36 2) all patients were aged ≥18 years and ≤80 years; 3) subjects had a body mass index (BMI) <28 kg/m 2 , which met the Chinese diagnostic standard for non-obesity. 37 The subject exclusion criteria were as follows: 1) individuals with other types of diabetes, including type 1 diabetes, gestational diabetes, and other specific types of diabetes; 2) patients with acute complications of diabetes, such as hyperosmolar hyperglycemic syndrome, ketoacidosis, and hypoglycemia; 3) patients with a history of chronic kidney disease, severe hepatic or renal insufficiency, and those undertaking a uric acid-lowering therapy; 4) patients with severe cardiac diseases, acute cerebrovascular diseases, tumor, and psychosis.…”
Section: Participantsmentioning
confidence: 99%
“…At low levels, this molecule also leads to increased insulin resistance [ 68 ]. Among Chinese individuals, Liu et al [ 69 ] found in a cross-sectional study that serum irisin levels are inversely correlated with dyslipidemia. Lack of exercise is the main cause of lower irisin levels, which connects intimately with protein and muscle mass loss in the occurrence of sarcopenia.…”
Section: General Aspects Of Sarcopenia Metabolic Repercussions and Or...mentioning
confidence: 99%
“…Fetuin-A has been shown to have a high association with non-alcoholic fatty liver disease. This metabolic pattern occurs by virtue of the increase in the amounts of fetuin-A interfering with the insulin signaling cascade and the translocation of GLUT-4 in the insulin target tissues and, as a consequence, causing damage to the pancreatic β cells [ 69 , 100 , 101 ].…”
Section: General Aspects Of Sarcopenia Metabolic Repercussions and Or...mentioning
confidence: 99%